FUNDAMENTALS OF ELECTRICAL ENGINEERING - Rizzoni, Giorgio; Kearns, James (McGraw-Hill Education, 2022)
Fundamentals of Electrical Engineering represents an effort to make the principles of electrical and computer engineering accessible to students in various engineering disciplines. The principal objective of the book is to present the fundamentals of electrical, electronic, and electromechanical engineering to an audience of engineering majors enrolled in introductory and more advanced or specialized electrical engineering courses. A second objective is to present these fundamentals with a focus on important results and common yet effective analytical and computational tools to solve practical problems. Finally, a third objective of the book is to illustrate, by way of concrete, fully worked examples, a number of relevant applications of electrical engineering. These examples are drawn from the authors' industrial research experience and from ideas contributed by practicing engineers and industrial partners.